Levantamento, análise e descrição de elementos paralinguísticos do português espontâneo - BULHÕES, Jailma do Socorro Uchôa (2006)
Natural speech contains paralinguistic aspects that do not belong to the arbitrary conventional code of language, but which nevertheless are meaningful and important in speech communication. These aspects are non-lexical utterances that function as full speech acts in the intersubjective communicative interaction. In respect these non-verbal details, Campbell (2002a, 2002b, 2003, 2004), Maekawa (2004), Fujie et al. (2004), Hoult (2004), Key (1958) apud Steimberg (1988) argue they contribute to expressive speech. In accord to these authors, it‟s the paralanguage phenomenon that signalizes information about speaker‟s attitude, opinions and emotions. In this way, we investigate, in this work, the common paralinguistic utterances in informal conversation in order to demonstrate its expressive function in speech signal. We identified 450 paralinguistic utterances in samples of natural speech of the Paraense Regional Portuguese and submitted them to a phonetic analysis. The analysis showed us that fundamental frequency and duration have strong effects in conveying paralinguistic phenomena in speech. Besides, we also identified another common property of the paralinguistic tokens: the syllabification. After analysis process, we described the usage and function of these non-lexical utterances and its contribution to the expressive speech. The results indicate that paralinguistic tokens signalize recognition, comprehension and attention, manage interpersonal relations and express emotion, attitude, and affect.